Lemierre's syndrome resulting from streptococcal induced otitis media and mastoiditis: a case report - Harris, Che M; Johnikin, Micean; Rhodes, Hope; Fuller, Theresa; Rana, Sohail R; Nabhani, Hasan; Hussain, Dulara; Kurukumbi, Mohan; Jayam-Trouth, Annapurni; Gajjala, Jhansi; Farhat, Faria; Mody, Vinod (Journal of medical case reports, 2009)
Lemierre's syndrome is an extremely rare and almost universally fatal disease characterized as thrombophlebitis of the internal jugular venous system with subsequent metastatic infection. Fusobacterium necrophorum is the most common organism implicated in causation of Lemierre's syndrome. Group A Streptococcus has mainly been observed as a polymicrobial organism in the syndrome. We report a rare finding of a rare disease where Group A Streptococcus was the sole organism triggering Lemierre's syndrome. To our knowledge, this is only the third recorded patient with such an occurrence. We describe a 9-year-old African American boy, who presented with otitis media and mastoiditis that culminated in Lemierre's syndrome. Isolates bore only Group A Streptococcus. The patient was appropriately treated and responded with full recovery from the syndrome. Since Lemierre's syndrome is classically detected by clinical diagnosis, these findings should prompt clinicians to consider Group A Streptococcus as an alternative catalyst. It should be pondered that patients who present with typical Group A streptococcal infections have the possibility for developing Lemierre's syndrome. Though this complication appears to be rare, early diagnosis and prompt intervention have proven critical in survival outcome. Indeed, what would seem to be a routine case of strep throat or otitis media easily treated with antibiotics could end up being an unalterable progression to death unless Lemierre's syndrome is immediately diagnosed and treated.